Large-scale slope failure and active erosion occurring in the southwest Ryukyu fore-arc area - T. Matsumoto; M. Kimura; M. Nakamura; T. Ono (Natural Hazards and Earth System Sciences, 2001)
The southwestern Ryukyu area east of Taiwan Island is an arcuate boundary between Philippine Sea Plate and Eurasian Plate. The topographic features in the area are characterised by (1) a large-scale amphitheatre off Ishigaki Island, just on the estimated epicentre of the tsunamigenic earthquake in 1771, (2) lots of deep sea canyons located north of the amphitheatre, (3) 15–20 km wide fore-arc basin, (4) 15–20 km wide flat plane in the axial area of the trench, (5) E-W trending half grabens located on the fore-arc area, etc., which were revealed by several recent topographic survey expeditions. The diving survey by SHINKAI6500 in the fore-arc area on a spur located 120 km south of Ishigaki Island was carried out in 1992. The site is characterised dominantly by rough topography consisting of a series of steep slopes and escarpments. A part of the surface is eroded due to the weight of the sediment itself and consequently the basement layer is exposed. The site was covered with suspended particles during the diving, due to the present surface sliding and erosion. The same site was resurveyed in 1997 by ROV KAIKO, which confirmed the continuous slope failure taking place in the site. Another example that was observed by KAIKO expedition in 1997 is a largescale mud block on the southward dipping slope 80 km south of Ishigaki Island. This is apparently derived from the shallower part of the steep slope on the southern edge of the fan deposit south of Ishigaki Island. The topographic features suggest N-S or NE-SW tensional stress over the whole study area. In this sense, the relative motion between the two plates in this area is oblique to the plate boundary. So, the seaward migration of the plate boundary may occur due to the gravitational instability at the boundary of the two different lithospheric structures. This is evidenced by a lack of accretionary sediment on the fore-arc and the mechanism of a recent earthquake which occurred on 3 May 1998 in the Philippine Sea Plate 250 km SSE of Ishigaki Island.